The effect of the self-directed learning (SDL) model integrated with peer teaching on environmental literacy - Sulistiyanto, Tabitha Qotrunnada; Sigit, Diana Vivanti; Aulya, Nailul Rahmi (Jurnal Inovasi Teknologi Pendidikan, 2025)
The escalating environmental issues in Indonesia highlight the need for early environmental education to cultivate environmental literacy, defined as a crucial attitude of environmental awareness, among students. An effective approach to cultivating environmental awareness through education is the Self-Directed Learning (SDL) model integrated with peer teaching, as this combined independent and collaborative method enhances students' sensitivity and independence in environmental problem-solving. This research aims to analyze the effect of implementing the SDL (Self-Directed Learning) model integrated with the peer teaching method on students' environmental literacy levels in the topic of environmental change. The research method employs a quantitative approach with a quasi-experimental design. The research sample consists of 36 students obtained through simple random sampling. The results of hypothesis testing indicate that the integration of SDL and peer teaching significantly contributes to improving students' environmental literacy. These findings imply that collaborative and independent approaches in learning can enhance students' understanding of environmental issues more effectively. Therefore, it can be concluded that the integrated SDL and peer teaching model can be applied to the topic of environmental change to foster students' environmental literacy. This study provides a foundation for future research to further develop the Self-Directed Learning (SDL) model integrated with peer teaching, exploring its application with diverse media and teaching materials across various subjects.